The Effectiveness of Cognitive Critical thinking Abilities in Nursing Education, A Systematic Review - Rasheed , Huda Mohammad Ali (Current Practice in Medical Science Vol. 8, 2022)
This study aims to critically describe and identify the effectiveness of critical thinking in nursing education. This study was a systematic descriptive appraisal conducted by collecting data from Ebooks and E-journals databases websites. The data was critically analyzed, evaluated, and discussed related to the effectiveness of critical thinking in nursing education findings based on evidence from other research studies. The result of this study showed that most of the research articles proved and gave backup support that critical thinking in nursing education is effective and accurate to be handled by nursing education, and critical thinking helps nursing students’ better understanding of the issues and can solve problems in clinical areas. In conclusion, this study agreed with the evidence the effect of critical thinking in nursing education is effective in nursing education and recommended that critical thinking can be part of the curriculum and enhanced faculties to promote students by identifying the problem and trying to solve it in clinical areas.